Redescription of two Australian cladocerans of the subfamily Aloninae Dybowski & Grochowski (Cladocera: Anomopoda: Chydoridae) - Sinev, Artem Y. (Zootaxa, 2022)
Morphology of two Australian water fleas, Alona rigidicaudis (Smirnov, 1971) and Coronatella (Coronatella) novaezealandiae (Sars, 1904) (Crustacea: Cladocera) was studied by optical and scanning electron microscopy. Morphology of the thoracic limbs was studied in detail. Previously unknown ephippial females and males are described for both species. Alona rigidicaudis is close in morphology to the simplex-group of the genus Anthalona Van Damme, Sinev & Dumont, 2011, but lack the main distinctive feature of Anthalona, the presence of cosmaria of lateral head pores. Morphology of Coronatella (Coronatella) novaezealandiae (Sars, 1904) is typical of the genus. Affinities and taxonomic position of studied species are discussed.